HEPATITIS-C GENOTYPES DISTRIBUTION IN PROVINCE OF PUNJAB, PAKISTAN - Ansari, Farheen; Nosheen, Rabia (Annals of Allied Health Sciences, 2022)
Objective: To determine the Hepatitis-C genotypes distribution in province of Punjab, Pakistan. Material & Methods: This comparative investigation was conducted at Jinnah hospital in Lahore over a period of 14 months (Aug 2016 to Sep 2017). All the patients’ referred to the Molecular Microbiology department of Jinnah hospital were enrolled for hepatitis C detection and genotyping. Results: Total no of 300 positive patients were enrolled in the study. 106 (35.33%) were males and 194 (64.66%) were female patients with different age group. Frequency rate of HCV Genotype 1 was 8.4% (25), Genotype 2 was 1.0% (3), and Genotype 3 was 81.0% (243), Genotype 4 was 2.33% (7), untype capable genotype was 5.33% (16), Cross contamination with genotype 1 and 2 was 0.67% (02), Cross contamination with genotype 1 and 3 was 1.33% (04). This examination exhibits that HCV effluence in contaminated people is recognized dominating to viral genotype 3 in Pakistan with the rate of 81.0% in the Lahore. Conclusion: Female population was viewed as logically affected with HCV when appeared differently in relation to male population. Since people developed among 36-45 years old are vibrant in public, they are in risk and acquire themselves.